Mapping vulnerable marine ecosystems to support conservation measures for Isidella elongata in the Southern Adriatic Sea - P. Carbonara; C. Ferrà; L. Marsaglia; R. Bakiu; A. Bellodi; I. Bitetto; G. Chimienti; M.C. Follesa; M. Kule; C. Neglia; W. Zupa; A.N. Tassetti (Journal of Environmental Management, 2026)

Space utilization by key species of the pelagic fish community in an upwelling ecosystem of the Mediterranean Sea - A. Bonanno; M. Barra; R. Mifsud; G. Basilone; S. Genovese; M. Di Bitetto; S. Aronica; G. Giacalone; I. Fontana; S. Mangano; R. Ferreri; M. Pulizzi; et al. (Hydrobiologia, 2018)

Changes in heat released by hydrothermal circulation monitored during an eruptive cycle at Mt. Etna (Italy) - I. S. Diliberto; E. Gagliano Candela; S. Morici; G. Pecoraino; S. Bellomo; M. Bitetto; M. Longo (Bulletin of Volcanology, 2018)

Variability of water mass properties in the Strait of Sicily in summer period of 1998–2013 - A. Bonanno; F. Placenti; G. Basilone; R. Mifsud; S. Genovese; B. Patti; M. Di Bitetto; S. Aronica; M. Barra; G. Giacalone; R. Ferreri; I. Fontana; et al. (Ocean Science, 2014)
The Strait of Sicily plays a crucial role in determining the water-mass exchanges and related properties between the western and eastern Mediterranean. Hydrographic measurements carried out from 1998 to 2013 allowed the identification of the main water masses present in the Strait of Sicily: a surface layer composed of Atlantic water (AW) flowing eastward, intermediate and deep layers mainly composed of Levantine intermediate water (LIW), and transitional eastern Mediterranean deep water (tEMDW) flowing in the opposite direction. Furthermore, for the first time, the signature of intermittent presence of western intermediate water (WIW) is also highlighted in the northwestern part of the study area (12.235° E, 37.705° N). The excellent area coverage allowed to highlight the high horizontal and vertical inter-annual variability affecting the study area and also to recognize the permanent character of the main mesoscale phenomena present in the surface water layer. Moreover, strong temperature-salinity correlations in the intermediate layer, for specific time intervals, seem to be linked to the reversal of surface circulation in the central Ionian Sea. The analysis of CTD data in deeper water layer indicates the presence of a large volume of tEMDW in the Strait of Sicily during the summers of 2006 and 2009.